Respuestas
Respuesta dada por:
1
Resolución:
![\frac{x}{3} - 1 = \frac{x}{5} - \frac{2}{3} \\ \frac{x - 3}{3} = \frac{3x - 10}{15} \\ 15(x - 3) = 3(3x - 10) \\ 15x - 45 = 9x - 30 \\ - 9x + 15x = - 30 + 45 \\ 6x = 15 \\ x = \frac{15}{6} \\ x = \frac{5}{2} \frac{x}{3} - 1 = \frac{x}{5} - \frac{2}{3} \\ \frac{x - 3}{3} = \frac{3x - 10}{15} \\ 15(x - 3) = 3(3x - 10) \\ 15x - 45 = 9x - 30 \\ - 9x + 15x = - 30 + 45 \\ 6x = 15 \\ x = \frac{15}{6} \\ x = \frac{5}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B3%7D+-+1+%3D++%5Cfrac%7Bx%7D%7B5%7D+-++%5Cfrac%7B2%7D%7B3%7D+%5C%5C++%5Cfrac%7Bx+-+3%7D%7B3%7D+%3D+%5Cfrac%7B3x+-+10%7D%7B15%7D+%5C%5C+15%28x+-+3%29+%3D+3%283x+-+10%29+%5C%5C+15x+-+45+%3D+9x+-+30+%5C%5C++-+9x+%2B+15x+%3D++-+30+%2B+45+%5C%5C+6x+%3D+15+%5C%5C+x+%3D+%5Cfrac%7B15%7D%7B6%7D+%5C%5C+x+%3D++%5Cfrac%7B5%7D%7B2%7D+)
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años